Elektrokoagulasi dalam pengelolaan air gambut: studi komparatif elektroda aluminium dan besi - Angga, Stevin Carolius; Hakim, Muh Supwatul; Arifin, Samsul; Dewi, Syahrani Riana; Resha, Enjel Elya; Manurung, Tety Wahyuningsih (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2025)
Water is essential for human life, yet several regions in Central Kalimantan face difficulties in accessing clean water and rely on peat water for daily needs. Peat water is generally unsuitable for drinking and sanitation purposes due to its poor quality. Its usage can lead to various health issues, such as digestive disorders skin diseases, tooth damage, and severe risks of heavy metal poisoning. One effective method to improve the quality of peat water is electrocoagulation. This study aims to investigate the effect of electrode variations using Al and Fe in treating peat water. Peat water samples were collected from Sebangau District, Palangka Raya, Central Kalimantan, in June 2024. The study analyzed water quality parameters, including TDS, pH, turbidity, color, COD, and dissolved Fe. The results showed that electrocoagulation increased pH to near-neutral levels and reduced turbidity, color, COD, and dissolved Fe, except for the Fe-Fe electrode combination, which caused an increase in TDS, color, and dissolved Fe. The Al-Al electrode combination proved to be the most effective in improving peat water quality.